2013
DOI: 10.1038/bjc.2013.92
|View full text |Cite
|
Sign up to set email alerts
|

Semiautomated isolation and molecular characterisation of single or highly purified tumour cells from CellSearch enriched blood samples using dielectrophoretic cell sorting

Abstract: Background:Molecular characterisation of single circulating tumour cells (CTCs) holds considerable promise for predictive biomarker assessment and to explore CTC heterogeneity. We evaluate a new method, the DEPArray system, that allows the dielectrophoretic manipulation and isolation of single and 100% purified groups of CTCs from pre-enriched blood samples and explore the feasibility of their molecular characterisation.Methods:Samples containing known numbers of two cell populations were used to assess cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
117
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(121 citation statements)
references
References 38 publications
2
117
0
1
Order By: Relevance
“…(Carpenter et al, 2014;Fabbri et al, 2013;Fernandez et al, 2014;Manaresi et al, 2003;Peeters et al, 2013;Polzer et al, 2014) Biophysical e Acoustophoresis Separates cells based on acoustophoretic mobility, which is size dependent, by exposing them to acoustic waves.…”
Section: Vortex Sizementioning
confidence: 99%
See 1 more Smart Citation
“…(Carpenter et al, 2014;Fabbri et al, 2013;Fernandez et al, 2014;Manaresi et al, 2003;Peeters et al, 2013;Polzer et al, 2014) Biophysical e Acoustophoresis Separates cells based on acoustophoretic mobility, which is size dependent, by exposing them to acoustic waves.…”
Section: Vortex Sizementioning
confidence: 99%
“…DEPArrayä is designed for single-cell recovery and not bulk enrichment of CTCs. Multiple clinical studies have used DEPArrayä to recover single CTCs for subsequent genetic analyses following enrichment using centrifugation or immunoaffinity (i.e., CellSearch) (Carpenter et al, 2014;Fabbri et al, 2013;Fernandez et al, 2014;Peeters et al, 2013;Polzer et al, 2014). The use of DEPArrayä technology for CTC recovery will likely be limited to samples with a relatively high number of CTCs (e.g., metastatic carcinomas) due to a cell-loss of approximately 40% during sample loading (Peeters et al, 2013).…”
Section: Dielectrophoresismentioning
confidence: 99%
“…[25] Many techniques have been developed and are under continuous improvement to enhance the efficacy of CTC isolation and enumeration. [16] Comparison of the OncoQuick density gradient method with FicollHypaque density gradients for separation of tumor cells from bone marrow and peripheral blood aspirates indicated that CTCs can be easily aspirated by both methods and analyzed further to determine their presence and quantity. [30] In the present study, we used the simple and cost-effective Ficoll-Hypaque density gradient method to separate PBMCs from whole plasma of cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…The CELLSEARCH ® system [34] is the only method approved by the US FDA for clinical use in metastatic breast, colorectal, and prostate cancer. [13,17,35] Patients with > 80 CTCs in 7.5 mL of blood were reported to die within one year of diagnosis from metastatic disease, [16] and CTCs continue to be detected after the first round of chemotherapy in some breast cancer patients with rapid progression of the disease to metastasis; [17] it has been suggested that, in such cases, it may be preferable to opt for an alternative treatment with novel therapeutic agents, rather than continuing with the same chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation